Enzymatic hydrolysates of mulberry leaf flavonoids alleviate depression induced by reserpine in zebrafish - ZHENG Xuan; LU Yunke; ZHOU Chunling; ZHANG Ju; WANG Mingxue; CUI Shizhan; JIA Dongsheng (Shipin yu jixie)
ObjectiveThis study aims to investigate the anti-depression effects of enzymatic hydrolysates of mulberry leaf flavonoids (EMLF).MethodsEMLF was prepared and its components were analyzed by UPLC-MS. A zebrafish model of depression was induced by 40 mg/L reserpine. Six groups were designed, including the control, model, fluoxetine, L-EMLF (20 μg/mL), M-EMLF (40 μg/mL), and H-EMLF (80 μg/mL) groups. Behavioral tests, including the new tank test and the light-dark box test, were conducted. The structural changes in the brain tissue of zebrafish in each group were observed by HE staining. The mRNA levels of interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), tryptophan hydroxylase-2 (TPH-2), and 5-hydroxytryptamine 2A (5-HT2A) receptor in the brain tissue were determined by q-PCR. The activity of superoxide dismutase (SOD) and the level of reactive oxygen species (ROS) in the brain tissue of zebrafish were measured. Metabolomics analysis was performed to identify differential metabolites and associated metabolic pathways.ResultsUPLC-MS identified 10 flavonoid aglycone compounds. Reserpine (40 mg/L) induced depression-like behaviors in zebrafish, while EMLF alleviated the bottom-dwelling and dark-preference behaviors, restored the orderly arrangement of nerve cells in the midbrain region, and increased the cell number. EMLF treatment down-regulated the mRNA levels of IL-1β, TNF-α, and 5-HT2A while up-regulating the mRNA level of TPH-2. In addition, EMLF increased the SOD activity and reduced the ROS level. Metabolomics analysis revealed that EMLF significantly regulated 24 differential metabolites, primarily affecting purine metabolism, arginine and proline metabolism, tryptophan metabolism, and riboflavin metabolism.ConclusionEMLF effectively alleviated reserpine-induced depression in zebrafish, potentially by regulating the tryptophan metabolism, purine metabolism, and arginine and proline metabolism.